Basic requirements to channel-forming equipment at mobile missile systems automation - Serbin, V. V.; Taraskin, N. V.; Sukhyi, V. V. (Видавництво Львівської політехніки, 2018)
When creating the missile units automated control systems, the information-management aspects emerge to prominence. Functional integration of all control means in order to increase the effectiveness of missile system employment is possible only on the basis of accomplishing the tasks of scientific-methodological and organizational-technical improvement of control system of missile unit forces and facilities and information support of command personnel decision-making system. The article deals with the basic requirements to channel-forming equipment that is installed on missile unit control means and fire means.
Keywords: automated control system; missile system; information interoperability; communication system; 681.518.5